El régimen de tenencia de la tierra en Costa Rica - González B, R. (Heredia (Costa Rica) : Universidad Nacional, 1993)
Sumario (Es)
Ilus.; 138 ref.
Keywords: TENENCIA; ESTRUCTURA AGRICOLA; ECONOMIA; SECTOR AGRARIO; EXPORTACIONES; COSTA RICA; PRODUCCION AGROPECUARIA